Perlindungan Konsumen terhadap Peredaran Kosmetik Ilegal di Pasar Tradisional Desa Moluo Gorontalo Utara - Rahmatiya Latif; Weny Almoravid Dungga; Sri Nanang M. Kamba (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research aims to analyze the forms of legal protection for consumers in the case of illegal cosmetic circulation in the Traditional Market of Moluo Village, Kwandang District, North Gorontalo Regency, and to examine the roles of the Health Department and the Gorontalo Food and Drug Supervisory Agency (BBPOM) in supervising and guiding business actors. The research method used is empirical legal research with a non-doctrinal qualitative approach, thru interviews with sellers, consumers, and supervisory authorities, as well as field observations and document studies. The research results show that the majority of vendors in the market already understand the importance of a distribution permit from BPOM and choose to sell legal products, although in practice illegal cosmetics are still found due to high consumer demand for instant results. The main obstacle lies in consumers who are often aware of the dangers of illegal cosmetics but still purchase them. BPOM Gorontalo implements legal protection thru two channels: preventive measures such as socialization, education, and routine inspections, and repressive measures such as legal action in accordance with Article 435 of Law Number 17 of 2023 concerning Health. The implications of this research confirm the need for more comprehensive legal protection strategies with cross-agency collaboration, increased public legal literacy, and consumer empowerment to make them more critical in product selection.